Codon-Specific Translation by m1G37 Methylation of tRNA - Hou, Ya-Ming; Masuda, Isao; Gamper, Howard (Frontiers in Genetics, 2019)
Although the genetic code is degenerate, synonymous codons for the same amino acid are not translated equally. Codon-specific translation is important for controlling gene expression and determining the proteome of a cell. At the molecular level, codon-specific translation is regulated by post-transcriptional epigenetic modifications of tRNA primarily at the wobble position 34 and at position 37 on the 3'-side of the anticodon. Modifications at these positions determine the quality of codon-anticodon pairing and the speed of translation on the ribosome. Different modifications operate in distinct mechanisms of codon-specific translation, generating a diversity of regulation that is previously unanticipated. Here we summarize recent work that demonstrates codon-specific translation mediated by the m1G37 methylation of tRNA at CCC and CCU codons for proline, an amino acid that has unique features in translation.